THE DEVELOPMENT OF HISTORICAL THINKING AND SKILLS IN THE TEACHING OF HISTORY IN THE SENIOR SECONDARY SCHOOL CURRICULUM IN INDONESIA - Hasan, Said Hamid (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2010)
The present study analyses history education as it is in curriculum document of senior secondary school. The curriculum document is a part of content standard document which is officially announced by Minister of National Education Regulation number 22 year 2005. This official document contains amongst others curriculum structure, competency standards and basic competency. Two major questions this study asks are (1) what is the concept of history education stipulated in curriculum document?, and (2) how far the existing curriculum provides possibilities for the development of historical thinking and skills? The questions are answered by analysing the document. Considering the characteristic of curriculum document which is an official document and all ideas are planned strictly and clearly written, the analysis uses logical analysis approach where the two research questions serve as analysis framework. The result shows that the exisiting curriculum conceived history education as a scientific discipline education. Also, the curriculum provides an ample opportunity to develop historical thinking and skills. Design used by the curriculum is concecutive design for the development of thinking and learning skills. It concluded that the concept of history education as a scientific discipline education is appropriate considering the objective of senior secondary education to prepare the students for university education. The study also suggests teachers of history to implement integrated design for the development of historical thinking and skills as an alternative to consecutive design.